Crystallographic structure of Ti-6Al-4V, Ti-HP and Ti-CP under high-pressure - Halevy, I.; Zamir, G.; Winterrose, M.; Sanjit, G.; Grandini, Carlos Roberto [UNESP]; Moreno-Gobbi, Ariel (IOP Publishing, 2010)
The phase stability of a commercial purity (Ti-CP), high purity (Ti-HP) and Ti-6Al-4V alloy were investigated in a diamond anvil cell up to 32 GPa and 298 K using a polychromatic X-ray beam. The Ti-CP and Ti-HP shown the same HCP (c/a∼0.632) to Hexagonal (c/a∼1.63) non reversible martensitic transition at about 9 GPa. The as received Ti-6Al-4V shows a very low relative volume fraction β-Ti / α-Ti. No phase changes were observed in the Ti-6Al-4V alloy in the pressure range of this study. The α phase of the Ti-6Al-4V shows monotonic volume cell pressure dependence. This volume change is reversible and non-hysteretic. The cell of the a phase recovered its original volume when the pressure was released. © 2010 IOP Publishing Ltd.
Keywords: Cell pressure; Commercial purity; Crystallographic structure; Diamond-anvil cell; High purity; Martensitic transitions; NO phase; Polychromatic x-rays; Pressure ranges; Ti-6al-4v; Ti-6Al-4V alloy; Volume change; Aluminum; Phase stability; Titanium alloys; Vanadium alloys